Feedback and Ballooning Instabilities in the Magnetosphere‐Ionosphere Coupling. Issue 12 (19th June 2020) - Watanabe, T.‐H.
Abstract: A unified model for the feedback and ballooning instabilities in the magnetosphere‐ionosphere (M‐I) coupling is developed by means of the reduced magnetohydrodynamic and two‐fluid equations, involving the local current closure and the ionospheric conductivity change in a scale of auroral fine structures, self‐consistently. In a low pressure gradient case, the Alfvén harmonics are destabilized through the feedback mechanism, while the ballooning instability appears if the magnetospheric pressure gradient exceeds a critical value. Transition of the dominant instability between the feedback and ballooning modes is brought by change of the normalized pressure gradient or the convection electric field in the magnetosphere. The obtained results imply a variety of appearance of auroral arcs and beads in the M‐I coupling system. Plain Language Summary: A novel explanation on generation of arc and beading structures of auroras is provided by means of theoretical analysis based on the first principle of plasma physics. The theory predicts competition of two different types of perturbation growth, leading to a variety of auroral appearance. Key Points: A new magnetosphere‐ionosphere coupling model is derived, where the feedback and ballooning instabilities are simultaneously described Transition of dominant instability mode is brought by change of pressure gradient or convection electric field in the magnetosphere The magnetosphere‐ionosphere coupling theory predicts a novel scenario on the auroral beading and preexisting arcs